Menace II Society - Hughes, Albert, 1972-; Lu, June Kyoto; Larenz Tate; Tyrin Turner (USA New Line Cinema, 1993)
This urban nightmare chronicles several days in the life of Caine Lawson, following his high-school graduation, as he attempts to escape his violent existence in the projects of Watts, CA.
A young street hustler attempts to escape the rigors and temptations of the ghetto in a quest for a better life.
Allen Hughes
Language(s): English Subtitle(s): No Subtitle
Keywords: Drama; Thriller; Crime